Peran Pemerintah Kota Semarang dalam Pemberantasan Pungutan Liar Di Pelayanan Publik (Studi Kasus : Pelayanan Perizinan Izin Mendirikan Bangunan Di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kota Semarang) - Dhani Rutdatin; Puji Astuti; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
AbstractPublic Service in providing licensing services are now familiar with theattendant bureaucracy which often provide a very complicated procedure. This studywill reveal the performance of public services in providing licensing servicesBuilding Permit (IMB) as an indicator of good governance. This study aimed toanalyze the efforts and the factors that hinder the Semarang city government incombating illegal fees in licensing services Building Permit at the Department ofInvestment and Integrated Services One Stop Semarang. In this study, researchersused a descriptive approach qualitative research methods, the research illustrates aphenomenon that has been going on and analyze the phenomenon through qualitativeresearch procedures. The results of this study in the realization of public servicessuch as service licensing, DPM_PTSP Semarang already provide a good enoughservice. Although in the realization of licensing services still do not meet the serviceof what has been determined in accordance with standards of public service, that isno problem at the speed of service and service schedule certainty. StandardOperating Procedure (SOP) has not run optimally, making it less effective andefficient in completing the work and the resulting deviant behavior extortion andkickbacks to the official community care givers.Keywords: public service, licensing services